Lymphangiogenesis and Its Correlation with the VEGF Expression and the Sentinel Lymph Node in Cutaneous Melanomas - Buzrla, Petr (Hindawi Publishing Corporation, 2014)
The aim of the study is to evaluate the density of intratumoral and peritumoral lymphatic vessels in primary cutaneous melanomas and to assess their correlation with the status of sentinel lymph nodes and the VEGF expression in tumor cells and stromal cells. A total of 40 patients were enrolled in the study: the melanomas were radically excised with the extirpation of the sentinel lymph node. The study subjects were divided into two groups: 20 cases with positive and 20 cases with negative sentinel lymph node results. The density of lymphatic vessels was evaluated by the antibody D2-40 and the VEGF expression was investigated in the semiquantitative way. The VEGF expression in melanoma cells and the stromal cells was negative to variable positive at both SLN negative and SLN positive patients in all pT stages. In the group of SLN positive patients, the density of intratumoral lymphatic vessels was low up to moderate, while it was observed to be absent, somewhere on the low level in the group of SLN negative patients. On the other side, the density of peritumoral lymphatic vessels was equally numerous at both SLN negative and SLN positive patients. The lymphatic invasion was found out at 4 SLN positive patients only. The ulceration was chiefly in the group of LN positive patients. The results show that the density of lymphangiogenesis and the intensity of the VEGF expression are considered to be an unreliable predictor of melanoma metastasis to the sentinel lymph node, but the ulceration and the lymphatic invasion can predict the potential for metastasis.